CONTRIBUTION OF CARBONATE ACCUMULATION RATE TO DECLINE IN CONCENTRATION OF PHOSPHORUS IN LAKE SEVAN - Mel'nichuk V.I.; Reznikov S.A.; Ul'yanova D.S.; Treshnikov A.F. (My University, 1989)
The eutrophication of Lake Sevan that has resulted from the drawdown of its level has destabilized the calcium carbonate systems, which in turn has affected the precipitation of calcium carbonate by disrupting the natural equilibrium between the rates of its generation and deposition. An investigation of hydrochemical conditions beginning in the period before drawdown of the water level in the lake identified a declining trend in the concentrations of phosphate, calcium, and HCO3- in the lake. Our investigation of bottom sediments, together with measurements of the change in the chemical composition of water in the lake, can be used to compare the rate of irreversible binding of phosphorus in bottom sediments with the changes in chemical properties of the water. Our investigations of bottom sediments indicate that independent mineralogical forms of phosphorus compounds can be formed and that phosphate can also be absorbed by calcium carbonate. It is thus established that the deposition of autochthonous calcium carbonate is capable of regulating the phosphorus content of the water of Lake Sevan and of affecting the bioproductivity of this lake.